2016
DOI: 10.1007/s10687-016-0256-2
|View full text |Cite
|
Sign up to set email alerts
|

Weak properties and robustness of t-Hill estimators

Abstract: We describe a novel method of heavy tails estimation based on transformed score (t-score). Based on a new score moment method we derive the t-Hill estimator, which estimates the extreme value index of a distribution function with regularly varying tail. t-Hill estimator is distribution sensitive, thus it differs in e.g. Pareto and log-gamma case. Here, we study both forms of the estimator, i.e. t-Hill and t-lgHill. For both estimators we prove weak consistency in moving average settings as well as the asymptot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Many data are aggregated by an inappropriate statistic (e.g. the arithmetic mean) which fails to address extremes severely (Beran et al, 2014;Stehlík et al, 2016a, b;Jordanova et al, 2016). Aggregation data statistics can have very different properties for sparse and dense data (Stehlík, 2016), which in the case of for example complicated medical images needs a very careful choice of method (Hermann et al, 2015).…”
Section: Ecology and Medicinementioning
confidence: 99%
“…Many data are aggregated by an inappropriate statistic (e.g. the arithmetic mean) which fails to address extremes severely (Beran et al, 2014;Stehlík et al, 2016a, b;Jordanova et al, 2016). Aggregation data statistics can have very different properties for sparse and dense data (Stehlík, 2016), which in the case of for example complicated medical images needs a very careful choice of method (Hermann et al, 2015).…”
Section: Ecology and Medicinementioning
confidence: 99%
“…Motivated by the fact that asymptotic bias and variance of existing estimators of ρ are high, the authors of Gomes et al (2000) considered the estimator γ G k n ,n (−1) ≡ H L k n ,n . We observed that Theorem 1 in Jordanova et al (2016) is a direct consequence of the distributional representation of H L k n ,n provided in Gomes et al (2000), see (2.11) therein. We also recognize a numerical typo in variance in Theorem 1 (Jordanova et al 2016), where the asymptotic variance 8 should be replaced by 5.…”
Section: Theoretical Motivation Of T-lghill Estimatormentioning
confidence: 82%
“…We have found that the estimator H L k n ,n was firstly developed in Gomes et al (2000), see (2.10) therein. We have not been aware of this fact in time of publication of Jordanova et al 2016, where we developed the estimator H L k n ,n , see Theorem 1 in Jordanova et al (2016).…”
Section: Theoretical Motivation Of T-lghill Estimatormentioning
confidence: 99%
See 1 more Smart Citation
“…Other consistent estimator of α for the moving average process (4) is the t-lgHill estimator introduced in Jordanova et al [14]. It is given by:…”
Section: Defining the Estimator And Main Resultsmentioning
confidence: 99%